Advances in 4-Hydroxyphenylacetate-3-hydroxylase Monooxygenase - Kai Yang; Qianchao Zhang; Weirui Zhao; Sheng Hu; Changjiang Lv; Jun Huang; Jiaqi Mei; Lehe Mei (Molecules, 2023)
Catechols have important applications in the pharmaceutical, food, cosmetic, and functional material industries. 4-hydroxyphenylacetate-3-hydroxylase (4HPA3H), a two-component enzyme system comprising HpaB (monooxygenase) and HpaC (FAD oxidoreductase), demonstrates significant potential for catechol production because it can be easily expressed, is highly active, and exhibits ortho-hydroxylation activity toward a broad spectrum of phenol substrates. HpaB determines the ortho-hydroxylation efficiency and substrate spectrum of the enzyme; therefore, studying its structure–activity relationship, improving its properties, and developing a robust HpaB-conducting system are of significance and value; indeed, considerable efforts have been made in these areas in recent decades. Here, we review the classification, molecular structure, catalytic mechanism, primary efforts in protein engineering, and industrial applications of HpaB in catechol synthesis. Current trends in the further investigation of HpaB are also discussed.